Subclinical elevation of plasma C-reactive protein and illusions/hallucinations in subjects with Parkinson's disease: case-control study. - Hideyuki Sawada (Public Library of Science (PLoS), 2014)
Background Though infections are associated with psychotic symptoms, whether or not subclinical inflammation is associated with hallucinations is not known in Parkinson's disease (PD). Purpose To investigate the association of illusions/hallucinations and plasma CRP levels in PD patients without symptomatic infections. Methods PD patients not diagnosed as having infections were assessed for illusions and hallucinations using the Parkinson Psychosis Questionnaire (PPQ). It comprises four-domain questions: PPQ-A for sleep problems, PPQ-B for hallucinations/illusions, PPQ-C for delusions, and PPQ-D for disorientation. Assigning patients with ≥1 points in the PPQ-B score to be cases and others as controls, the association of hallucinations/illusions and clinical features (age, sex, duration of PD, Unified Parkinson's Disease Rating Scale part 3 (UPDRS-3), Mini-Mental State Examination (MMSE) score, sleep disturbance (PPQ-A score) as well as daily doses of L-Dopa, dopamine agonists, amantadine, and selegiline) were analyzed using a case-control design. Results A total of 111 patients were examined and plasma CRP levels were <0.1-6.0 mg/L. Hallucinations or illusions were detected in 28 (25.2%). There were significant differences in age, UPDRS-3 score, MMSE score, PPQ-A, daily doses of L-Dopa and dopamine agonists and plasma CRP levels between cases and controls. A multivariate logistic regression model revealed that UPDRS-3 scores and plasma CRP levels were significantly associated with hallucinations/illusions with an adjusted odds ratio of 1.96 (95% confidence interval (CI) 1.20-3.20) per 10 points and 1.57 (95% confidence interval 1.13-2.16) per two-fold, respectively. Dividing patients into thirds by CRP levels (≤0.2, 0.3-0.6, ≥0.7 mg/L), the prevalence of hallucinations/illusions was 13.2%, 21.6%, and 41.7%, in the bottom-, middle-, and top-thirds, respectively (for trend p = 0.012). Conclusions Subclinical elevation of plasma CRP levels was associated with hallucinations or illusions after adjustment for motor disability, suggesting that subclinical elevations of CRP levels might be an independent risk for hallucinations/illusions.